MANAGEMENT OF PROMOTION OF ORGANIC PRODUCTS AND THE ROLE OF EDUCATIONAL INSTITUTIONS IN SERBIA - Tomić, Gordana; Đurica, Maja; Bugar, Denis (Economics of Agriculture, 2018)
Organic agriculture contributes to the reduction of environmental pollution, provides supply of customers with quality products, affects agriculture to be more competitive and affects rural development. All involved parties are satisfied with such agriculture, that is, it helps state (national government) to preserve its resources. Secondly, consumers receive healthy food and food producers gain higher profits. To get the culture and the habit of organic food consumption younger population education should start in order to get them used to the fact that organic food presents a source of human health and the environment. Therefore, in Serbia the action of introduction and promotion of organic products should be initiated (especially fresh fruit and vegetable) by the educational institutions.